Pencegahan Stunting Melalui Kegiatan Sosialisasi Hidup Sehat dan Makanan Bergizi di Desa Tirtanadi Kecamatan Labuhan Haji - Ni Komang Tri Dharmayani; Erwin Jayadi Putra; Nurlely Shabna Syundari; Baiq Nurmayana; Ira Agustina; Nur Indrianingsih M.G Indrianingsih; Ernidasari Rohmati; Devy Febriana; Kadek Yefta Christian; Ridho Abdi Saputra (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2022)
Stunting is a chronic nutritional problem resulting from a state of malnutrition that lasts long enough. One area in Indonesia that still faces stunting problems is Tirtanadi village, Labuan haji sub-district, East Lombok district, West Nusa Tenggara province. Factors that cause stunting are low understanding of stunting and poor sanitation. Both of these things lead to a lack of nutritional intake for infants, children, and pregnant women. One of the efforts to prevent stunting can be done by utilizing agricultural products to be processed high in nutrition. Tirtanadi Village is a producer of corn as the main agricultural product and has not been used optimally. Corn is processed into various types of food such as pudding and corn nuggets with a high taste. The utilization of corn in processed food with a preferred taste can be done to increase the family's nutritional intake while at the same time increasing the family's economy.